ANALYSIS OF STUDENTS' ERRORS IN SOLVING ADDITION AND SUBTRACTION PROBLEMS USING THE NEWMAN TECHNIQUE - Lien Malinda; Sufyani Prabawanto; Rusdiono Muryanto (Jurnal Cakrawala Pendas, 2026)
The ability to solve mathematical word problems is an important skill for elementary school students because it involves contextual understanding and mathematical reasoning. However, in practice, students still often make mistakes in solving addition and subtraction word problems. This study aims to analyze the types and patterns of errors made by third-grade elementary school students in solving addition and subtraction word problems based on Newman's technique stages. This study used a descriptive qualitative approach with third-grade elementary school students in Sumedang Regency as subjects. Data were obtained through a written test consisting of three contextual word problems that were completed individually. Data analysis was carried out by identifying errors in the stages of reading, understanding the problem, transformation, process skills, and writing the final answer. The results showed that the most dominant errors occurred at the problem comprehension and transformation stages, especially in interpreting keywords and determining the correct mathematical operations. Errors at the process skills and final answer writing stages were also found, but these tended to be a consequence of previous errors. The conclusion of this study shows that students' errors in word problems are not only caused by their arithmetic abilities, but are more influenced by their weak contextual analysis and mathematical reasoning skills. Mathematics learning needs to emphasize the strengthening of mathematical literacy and the use of the Newman Technique as a tool for diagnosing students' learning difficulties.